Scenario-Based Algorithmics: Coding Algorithms by Automatic Composition of Separate Concerns. - Harel, David; Marron, Assaf; Yerushalmi, Raz (Computer (00189162), 2021)
A method for programming reactive systems, called scenario-based algorithmics, can have several advantages, both in programming and in computer science education. We provide new examples, experiments, and perspectives.